2011
DOI: 10.4081/jlimnol.2011.293
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between microbial degradation of sedimentary organic matter and lake hydrodynamics in shallow water bodies: insights from Lake Sarbsko (northern Poland)

Abstract: In this paper we demonstrate spatial and seasonal changes in the pathways of microbial decomposition of organic matter within the surface sediments of Lake Sarbsko, a coastal water body located on the middle Polish-Baltic coast. We studied lake waters and bottom sediments at 11 sampling stations throughout the basin and in different seasons between November 2007 and September 2008. It was established that, in this very productive and shallow lake, microbial activity increases in warmer seasons and ceases durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The organic matter content was obtained via thermal combustion (Heiri et al 2001). Terrigenous (SiO 2ter ) and biogenic (SiO 2biog ) silica were analysed as in Woszczyk et al (2011). The total carbon (TC), total sulphur (TS) and total nitrogen (TN) were determined using a Vario Max elementary analyser (Elementar Analysensysteme).…”
Section: Geochemical Datamentioning
confidence: 99%
“…The organic matter content was obtained via thermal combustion (Heiri et al 2001). Terrigenous (SiO 2ter ) and biogenic (SiO 2biog ) silica were analysed as in Woszczyk et al (2011). The total carbon (TC), total sulphur (TS) and total nitrogen (TN) were determined using a Vario Max elementary analyser (Elementar Analysensysteme).…”
Section: Geochemical Datamentioning
confidence: 99%
“…Thus, our results have shown that on average during the study period the higher number of microorganisms and their community activity, with prevailing anaerobic processes, occurred in the littoral sediments of A. negundo leaf litter accumulation zone than in sediments of the river close by riparian native tree location. In shallow zones, anaerobic processes have negative consequences, because they promote the accumulation of fermentation products and other intermediate mineralization compounds (Kuznetsov et al, 1985) as well as benthic phosphorus release (Woszczyk et al, 2011), which, in its turn, may stimulate secondary eutrophication and littoral silting. On the other hand, increasing anaerobic sulfate reduction accelerates the growth of hydrogen sulfide concentration what in the future may have a negative impact on the quantitative and qualitative structure of benthic organisms.…”
Section: Datementioning
confidence: 99%
“…The lake area is 6.5 km 2 and its average depth is 1.4 m with a maximum of 3.5 m in the mid-eastern section of the basin (Figure 1) (Woszczyk et al 2011). The lake is fed by the Chełst River from the east and a few irrigation channels from the south (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…As Lake Sarbsko has no direct connection to the Baltic Sea, freshwater inflow has the greatest influence on the chemical composition of its water, which reveals relatively low chloride concentrations (5.7-97.7 mg L -1 ) (Woszczyk et al, 2011). However, during severe winter storms marine waters may enter the lake via the Łeba river mouth and the Chełst outflow channel slightly raising its salinity.Marine influences in the lake are also reflected in the seasonal variations of the water level, which clearly coincide with fluctuations of the Baltic level (Woszczyk et al 2010).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation